PENERAPAN DISCOVERY LEARNING DALAM BERMAIN SEPAK BOLA UNTUK MENINGKATKAN KEMAMPUAN MENCETAK GOL - Manalu, Nimrot; Sijabat, Togu; Hia, Jevan Novtriman; Aritonang, Tri Suci; Nabila, Vina (Universitas Negeri Medan, 2025)
Orientation in soccer learning with the Discovery Learning approach aims to develop students' ability to score goals, not only in terms of physical, but also in terms of tactical and strategic understanding. This study uses a descriptive qualitative research method, which focuses on collecting narrative data to provide a deeper understanding of the phenomenon being studied. The results of this study, namely playing soccer with a goal-scoring orientation based on Discovery Learning means implementing a learning approach where players find strategies and techniques for scoring goals through exploration, experience, and reflection.